Dissemination of Newcastle disease virus (NDV-AF2240) in liver during intratumoral injection of xenotransplant breast cancer in BALB/c mice. - Motalleb, Gholamreza; Othman, Fauziah; Ideris, Aini; Rahmat, Asmah (Royan Institute, Iranian Academic Center for Education Culture and Research, 2009)
Objective: Newcastle disease virus (NDV) or avian paramyxovirus type1 possesses several unique properties that make it an excellent anticancer agent. The hemagglutinin neuraminidase (HN) protein of NDV plays an important role in viral infection. The purpose of the present study is to investigate the dissemination of Newcastle disease virus (NDV) AF2240 strain in the liver during intratumoral injection in 4T1 breast cancer in female BALB/c mice.